On granular derivatives and the solution of a granular initial value problem - Batyrshin, Ildar (Zielona Góra: Uniwersytet Zielonogórski)
Perceptions about function changes are represented by rules like "If X is SMALL then Y is QUICKLY INCREASING." The consequent part of a rule describes a granule of directions of the function change when X is increasing on the fuzzy interval given in the antecedent part of the rule.
Keywords: fuzzy differential; fuzzy granule; initial value problem; cylindrical extension